PENGEMBANGAN KOMPETENSI BIDANG MANAJEMEN SUMBER DAYA MANUSIA DAN MANAJEMEN PEMASARAN MELALUI CENTER Of BUSINESS AND MANAGEMENT (CoBM) - Arniati, Tutik; Bagyo, Yupono; Rahmawati, Rina; Ratnasari, Siwi Dyah (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
The purpose of PPUPIK is to establish a business unit called the Center of Business and Management (CoBM) which provides training services and work practices in Human Resources Management and Marketing Management in accordance with the Indonesian National Work Competency Standards (SKKNI) and the Indonesian National Qualification Framework (KKNI) in order to improve the competence of students, tertiary education graduates and industrial employees in accordance with the competency requirements required by the world of work. The method used in this PPUPIK is through training and work practices in work laboratories that are designed the same as activities that occur in the real workplace according to BNSP standards through training and work practices in the field of Human Resources and Marketing skills at the level of competence needed by the world of work. Lecturers who have been certified in their fields and good collaboration with practitioners are expected to make this program closer to university graduates with the world of work. Expected outputs from PPUPIK are scientific articles published in ISSN journals, articles in print media, activity videos and training modules and design training models developed by the CoBM team. Increased collaboration and collaboration between universities and the industry and other universities are also expected from this program